Exposure classification of MRI workers in epidemiological studies. Issue 1 (24th April 2012) - Hansson Mild, Kjell; Hand, Jeff; Hietanen, Maila; Gowland, Penny; Karpowicz, Jolanta; Keevil, Stephen; Lagroye, Isabelle; van Rongen, Eric; Scarfi, Maria Rosaria; Wilén, Jonna
Abstract We estimate that there are about 100, 000 workers from different disciplines, such as radiographers, nurses, anesthetists, technicians, engineers, etc., who can be exposed to substantial electromagnetic fields (compared to normal background levels) around magnetic resonance imaging (MRI) scanners. There is a need for well‐designed epidemiological studies of MRI workers but since the exposure from MRI equipment is a very complex mixture of static magnetic fields, switched gradient magnetic fields, and radiofrequency electromagnetic fields (RF EMF), it is necessary to discuss how to assess the exposure in epidemiological studies. As an alternative to the use of job title as a proxy of exposure, we propose an exposure categorization for the different professions working with MRI equipment. Specifically, we propose defining exposure in three categories, depending on whether people are exposed to only the static field, to the static plus switched gradient fields or to the static plus switched gradient plus RF fields, as a basis for exposure assessment in epidemiological studies. Bioelectromagnetics 34:81–84, 2013. © 2012 Wiley Periodicals, Inc.